2017
DOI: 10.1038/s41598-017-15744-4
|View full text |Cite
|
Sign up to set email alerts
|

Excessive fuel availability amplifies the FTO-mediated obesity risk: results from the TUEF and Whitehall II studies

Abstract: Variation in FTO is the most important common genetic determinant of body weight. Altered energy metabolism could underlie this association. We hypothesized that higher circulating glucose or triglycerides can amplify the FTO impact on BMI. In 2671 subjects of the TUEF study, we investigated the interaction effect of fasting glucose and triglyceride levels with rs9939609 in FTO on BMI. We analysed the same interaction effect by longitudinally utilizing mixed effect models in the prospective Whitehall II study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
3
0
5
Order By: Relevance
“…Insulinogenic index (arbitrary units) as marker for insulin secretion is shown as hyperbolic function of insulin sensitivity (insulin sensitivity index, arbitrary units, unadjusted values). Subjects with normal glucose tolerance (NGT, age 18-50 years) from the German TUEF study (40) were used to compute the hyperbolic function (n=1421). The arrows represent baseline values (origin) and values after 12 months of intervention (end) in the study arms.…”
Section: Resultsmentioning
confidence: 99%
“…Insulinogenic index (arbitrary units) as marker for insulin secretion is shown as hyperbolic function of insulin sensitivity (insulin sensitivity index, arbitrary units, unadjusted values). Subjects with normal glucose tolerance (NGT, age 18-50 years) from the German TUEF study (40) were used to compute the hyperbolic function (n=1421). The arrows represent baseline values (origin) and values after 12 months of intervention (end) in the study arms.…”
Section: Resultsmentioning
confidence: 99%
“…A többféle gén számos allélvariánsa, az életmódi és egyéb környezeti faktorok (például étrend, fizikai aktivitás, negatív stressz, dohányzás, környezetszennyezés) változásai azonban együttesen már jelentős szerepet játszhatnak az adott betegség klinikai megjelenésében. Mindezen összefüggések a "gén-gén" és a "gén-környezet" interakció modellek alapját képezik [6,[8][9][10].…”
Section: öSszefoglaló Közleményunclassified
“…More interestingly, some studies found that METTL14 improves its translation efficiency without changing the mRNA expression level; that is, the target mRNA abundance remains unchanged ( 145 ). Preceding studies suggested that FTO mediates changes in energy metabolism to regulate weight and growth in adults ( 146 , 147 ). Recent studies found that the expression of FTO is upregulated in human breast cancer.…”
Section: A Mediated Metastasis In Cancersmentioning
confidence: 99%